LINE FORMATION IN SPECTRA OF X-RAY NOVAE - Suleimanov, V. F.; Shimansky, V. V. (Одеські астрономічні публікації, 2017)
Results of X-ray Novae (XN) optical spectra computation are presented. The continuum and Balmer line are calculated. The model of XN as a self-irradiated accretion disk is used. Local (for given radius) disk atmospheres as model stellar atmospheres, heated due to external X-ray radiation are treated. Changes of spectra shape and equivalent widths of the Balmer lines depending from the luminosity and some others accretion disk parameters are investigated. The comparison of GRO JO422+32 observed spectra with model spectra are curried out.